Bioactive compounds as potential alternative treatments to prevent cancer therapy-induced male infertility - Simón, Layla; Mariotti-Celis, María Salomé (Frontiers in Endocrinology, 2024)
About 8-12% of couples experience infertility, with male infertility being the cause in 50% of cases. Several congenital and acquired conditions, including chronic diseases and their treatments, can contribute to male infertility. Prostate cancer incidence increases annually by roughly 3%, leading to an increment in cancer treatments that have adverse effects on male fertility. To preserve male fertility post-cancer survival, conventional cancer treatments use sperm cryopreservation and hormone stimulation. However, these techniques are invasive, expensive, and unsuitable in prepubertal patients lacking mature sperm cells. Alternatively, nutritional therapies enriched with bioactive compounds are highlighted as non-invasive approaches to prevent male infertility that are easily implementable and cost-effective. In fact, curcumin and resveratrol are two examples of bioactive compounds with chemo-preventive effects at the testicular level. In this article, we summarize and discuss the literature regarding bioactive compounds and their mechanisms in preventing cancer treatment-induced male infertility. This information may lead to novel opportunities for future interventions.